An Innovative Design of a Solar Double-Chimney Power Plant for Electricity Generation - Emad Abdelsalam; Feras Kafiah; Fares Almomani; Muhammad Tawalbeh; Sanad Kiswani; Asma Khasawneh; Dana Ibrahim; Malek Alkasrawi (Energies, 2021)
The present work involves a new and novel upgrading design to the classical solar chimney power plant (SCPP) structure. The SCPP design was modified by adding a co-centric secondary external chimney to the SCPP structure to enhance energy production. In the new improved design, named the solar double-chimney power plant (SDCPP), the internal chimney, operates like a traditional SCPP to produce electricity during the daytime whereas the secondary external chimney operates as 10 cooling towers (CT) in a series. Each CT is equipped with a turbine and water sprinklers for further energy production. The new design offers the operation of the SCPP during the day and the continuous operation of the CT (day-and-night). A mathematical model that includes the energy and mass balance equations of the system was built using MATLAB. The SDCPP system produced up to 993 MWh of electrical energy, which is 2.6 times higher than the traditional SCPP (377 MWh). The new design configuration achieved a percentage of thermal efficiency (%ηth) of 1.6%, which is 200 times greater than the SCPP. The economic assessment of the new system revealed a 50% reduction in the localized cost of energy (LCOE) compared with traditional SCPP. The key advantage of the new design is related to the use of low-cost material in constructing the secondary chimney to reduce the fixed capital cost and prompt the economic feasibility of the system. Overall, the proposed SDCPP offers a feasible and economic solution to produce electricity and to potentially reduce greenhouse gas emissions.